2021
DOI: 10.3389/fonc.2021.629640
|View full text |Cite|
|
Sign up to set email alerts
|

The Deubiquitinating Enzyme UCHL1 Induces Resistance to Doxorubicin in HER2+ Breast Cancer by Promoting Free Fatty Acid Synthesis

Abstract: Ubiquitin C-terminal hydrolase L1 (UCHL1), which is a deubiquitinating enzyme, is known to play a role in chemoresistance in cancers. However, its potential roles and mechanisms in the chemoresistance of breast cancer (BC) remain unclear. In this study, we examined its expression in patients with BC and employed Kaplan–Meier analysis and the log-rank test for survival analyses. It was found that up-regulated UCHL1 expression was positively associated with both chemoresistance and poor prognosis, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Proteins enriched in EVs from women with obesity relative to women of a healthy weight are, for the most part, poorly characterized in the context of obesity and/or breast cancer. AKAP2 has been shown to be upregulated in ovarian cancer and promote cancer cell growth 45 , while UCHL1 has been shown to promote cancer stemness and chemoresistance 46,47 . Our in vitro and in vivo results point to a role for O-EVs in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins enriched in EVs from women with obesity relative to women of a healthy weight are, for the most part, poorly characterized in the context of obesity and/or breast cancer. AKAP2 has been shown to be upregulated in ovarian cancer and promote cancer cell growth 45 , while UCHL1 has been shown to promote cancer stemness and chemoresistance 46,47 . Our in vitro and in vivo results point to a role for O-EVs in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins enriched in EVs from women with obesity relative to women of a healthy weight are, for the most part, poorly characterized in the context of obesity and/or breast cancer. AKAP2 has been shown to be upregulated in ovarian cancer and promote cancer cell growth (Li et al , 2017), while UCHL1 has been shown to promote cancer stemness and chemoresistance (Lu et al , 2021; Tian et al , 2022). Our in vitro and in vivo results point to a role for O‐EVs in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several agents that target specific metabolic pathways, including fatty acid synthesis, have been shown to have the therapeutic potential to improve cancer treatment efficacy. A reduction of key enzymes in the DNL pathway has been shown to cause a reduction in fatty acid products [27] and fatty acid oxidation (FAO) [12], resulting in a decrease in the proliferative, metastatic and invasive ability of cancer cells [67][68][69][70][71][72][73][74][75][76]. The mechanism of the anticancer effect of EGCG has been demonstrated to be mediated via inhibiting the fatty acid biosynthesis pathway [50,[77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%